Improvement of lipoatrophy by switching from efavirenz to lopinavir/ritonavir. Issue 5 (10th September 2015) - Rojas, J; Lonca, M; Imaz, A; Estrada, V; Asensi, V; Miralles, C; Domingo, P; Montero, M; del Rio, L; Fontdevila, J; Perez, I; Cruceta, A; et al.
Abstract : Objective: To assess whether changes in antiretroviral drugs other than thymidine nucleoside reverse transcriptase inhibitors (NRTI) may have a body fat impact in HIV‐infected patients with lipoatrophy. Methods: Ninety‐six‐week phase IV, open‐label, multicentre, pilot randomized trial. HIV‐infected patients with moderate/severe lipoatrophy at one or more body sites despite long‐term thymidine NRTI‐free therapy were randomized to continue their efavirenz (EFV)‐based antiretroviral regimen or to switch from EFV to lopinavir/ritonavir (LPV/r). The primary endpoint was the absolute change in limb fat mass measured by dual X‐ray absorptiometry from baseline to 96 weeks. Changes in other body fat measurements, subjective perception of lipoatrophy, subcutaneous fat gene expression and plasma lipids were also assessed. Results: Thirty‐three patients (73% men, median age 52 years) were recruited. At 96 weeks, absolute limb fat mass increased in the LPV/r arm vs . the EFV arm (estimated difference +1082.1 g; 95% CI +63.7 to +2103.5; P  = 0.04); this difference remained significant after adjustment by gender, age, fat mass, body mass index and CD4 cell count at baseline. Subjective lipoatrophy perception scores also improved in the LPV/r arm relative to the EFV arm. Adipogenesis, glucose and lipid metabolism, and mitochondrial gene expression increased in the LPV/r arm compared with the EFV arm at 96 weeks. HDL cholesterol decreased in the LPV/r arm relative to the EFV arm. Conclusions: Switching from EFV to LPV/r in HIV‐infected patients with lipoatrophy may offer further limb fat gain beyond thymidine NRTI discontinuation, although this strategy decreased plasma HDL cholesterol and caused changes in subcutaneous fat gene expression that may be associated with increased insulin resistance.